Development and Performance Evaluation of a Rain Shade for a low scale Agricultural Produce - MN Akhaze; AA Bamidele (Journal of Applied Sciences and Environmental Management)
This paper reports on the development and performance evaluation of a rain shade for a low scale agricultural produce, The rain shade consists of a geared D. C motor, 12V battery, sensor, a roller tube in which a polyester fabric is wound, two extension arms attached directly to the roller tube that pulls out the fabric when the device is open to protect a designated area from rain and pulls it back when the rain stops and a stand. On performance evaluation of the rain shade, it was to able protect maize cobs by opening in average periods of 0.5,1,1 and 1 second and retracting in average periods of 150, 411,470 and 480 seconds respectively.